The Selection of Outstanding Teacher Analysis at SD Negeri 01 Perigi Using TOPSIS Method - Rahmawati, Diah; Wanda, Sulistianto Sutrisno (Universitas Trilogi, 2023)
Teacher is an important part in the process of teaching and learning activities with students. A teacher can be declared an achiever if he is able to complete the assigned task charged such as: teaching in class, personality and attendance. At the moment, SD Negeri 01 Perigi has 25 permanent teachers, and usually to chose the best teacher candidate uses a subjective judgments standards which is based on the closeness of teacher personnel. For this reason, further analysis is needed to overcome the subjectivity of the procedure selection of outstanding teachers by the principal as the decision maker. This research proposes a solution based on the problem that has been mentioned, namely by performing analysis using the TOPSIS method. The TOPSIS method ranked the final results of the selected alternatives which calculate the positive ideal distance and negative ideal distance. Criteria set at this research is used as a weighting that is Teacher Evaluation Value, Absence, Discipline, Technology Proficiency, Learning Innovation, and Pedagogic then matrix calculations are carried out which produced the ranking order to select the best alternative from a number of alternative solutions, based on the ideal solution distance. The results of this research are produced 10 ranking of outstanding teachers in the order of Syifa Habibah (0,739154498), Rista Mila Karmelia, S.Pd. (0,689946165), Lila Sakilla,S.Pd. (0,683915136), Arbaini,S.Ag. (0,674172212), Abdul Qodir, M.Ag. (0,64436484), Panji Wahyu Utomo (0,58496903), Nita Susanti,S.Pd. (0,560390869), Een Wahyuni,S.Pd (0,54050899), Uus Husna, S.Ag. (0,534886111), Nurbaiti,S.Pd. (0,506297247). The use of the TOPSIS method can assisting the Principal of SD Negeri Perigi 01 in providing recommendations for selection of outstanding teachers objectively at SD Negeri Perigi 01.